Pengaruh Profitabilitas Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility (Tanggung Jawab Sosial Perusahaan) Sebagai Variabel Moderating (Studi Empiris Di Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indo - Ali, Karnila; Fitriani, Fitriani; Sobri, Rian Mochammad (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine and analyze the effect of profitability on firm value withcorporate social responsibility as a moderating variable in food and beverage sub-sectormanufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. Thisresearch approach uses quantitative methods. The population in this study amounted to 30.The sampling technique used was purposive sampling, based on the purposive samplingtechnique, the sample obtained in this study amounted to 14 companies. The data analysismethod in this study was carried out using panel data testing, data processing was carriedout using the Eviews program. The results show that profitability has a significant effect onfirm value in food and beverage sub-sector manufacturing companies listed on the IndonesiaStock Exchange in 2017-2020 and Corporate Social Responsibility does not moderate theeffect of profitability on firm value in food and beverage sub-sector manufacturingcompanies. listed on the Indonesia Stock Exchange in 2017-2020.